Persistência da veia cava cranial esquerda em cão - Culau, Paulete de Oliveira Vargas (2021)
Background: Persistent left cranial vena cava with absent right cranial vena cava is a rare anomaly. Congenitally persistent left cranial vena cava is the most common variant of the systemic venous return to the heart, embryologically resulting from failure of the anterior cardinal vein in becoming obliterated. Persistent left cranial vena cava is the most common form of anomalous venous drainage involving the cranial vena cava, and represents persistence of the left horn of the embryonic sinus venosus, which normally involutes during normal development, becoming the coronary sinus. Usually, persistent left cranial vena cava enters the right atrium through the orifice of an enlarged coronary sinus. Persistent left cranial vena cava is an uncommon congenital cardiovascular anomaly in dogs, generally coexisting with other more serious cardiac defects. The condition is rare as an isolated single defect. The left cranial vena cava is observed only among domestic mammals, but it is a relatively rare anomaly that can be found in other species, including man, without causing clinical problems. The objective of this study was to report the occurence of a rare vascular formation of the cranial vena cava, which caused the persistence of the left cranial vena cava instead of the right one. Case: At the anatomy laboratory of the Faculty of Veterinary of the UFGRS, a male dog was identified with a persistent left cranial vena cava and absent right cranial vena cava. The left cranial vena cava started at the entry level of the thorax, ventral to the left side of the trachea, from the union of the right and left brachiocephalic veins. In the cranial mediastinum it was located on the dorsal surface of the left atrium of the heart, bypassing the pulmonary veins ventrally. It joined the great cardiac vein at the caudal part of the right atrium near the caudal vena cava, in the coronary sinus. During its route, the left cranial vena cava crossed the left aortic arch and pulmonary trunk. In the cranial mediastinum, it was joined by the left internal thoracic vein ventrally and, dorsally, by the vertebral and left costocervical veins. On the right side, the internal thoracic, vertebral and right costocervical veins joined together to form a vein which resulted in the right atrium with the azygos vein. Discussion: In birds and some mammals (rabbits, mice, guinea pigs, etc.) the right and left cranial vena cava are present. However, during the embryologic development of dogs, the cranial cardinal vein fuses, resulting in a single right cranial cardinal vein that will become the right cranial vena cava. The left cranial cardinal vein, caudal to the fusion, usually becomes atrophied. The caudal aspect of the left common cardinal vein persists, forming the coronary sinus. If there is a persistent left cranial vena, it will correspond to the left cranial vein which has not atrophied and retained its embryologic connection with the left common cardinal vein at the coronary sinus. Persistent left cranial vena cava with absent right cranial vena cava is a rare anomaly. Congenitally persistent left cranial vena cava is the most common variant of systemic venous return to the heart, embryologically resulting from failure of the left anterior cardinal vein to become obliterated. The blood from the right side is carried by the persistent left cranial vena cava to the right atrium through the coronary sinus. The dog had no congenital heart disease and the blood from the right side was drained by the persistent left superior vena cava into the right atrium through the coronary sinus. The dog was clinically normal and the unusual vessel was an incidental finding.